STAT5A is regulated by DNA damage via the tumor suppressor p53. (June 2016) - Mukhopadhyay, Utpal K.; Cass, Jamaica; Raptis, Leda; Craig, Andrew W.; Bourdeau, Véronique; Varma, Sonal; SenGupta, Sandip; Elliott, Bruce E.; Ferbeyre, Gerardo
Abstract: Here we report that the STAT5A transcription factor is a direct p53 transcriptional target gene. STAT5A is well expressed in p53 wild type cells but not in p53-null cells. Inhibition of p53 reduces STAT5A expression. DNA damaging agents such as doxorubicin also induced STAT5A expression in a p53 dependent manner. Two p53 binding sites were mapped in the STAT5A gene and named PBS1 and PBS2; these sites were sufficient to confer p53 responsiveness in a luciferase reporter gene. Chromatin immunoprecipitation experiments revealed that PBS2 has constitutive p53 bound to it, while p53 binding to PBS1 required DNA damage. In normal human breast lobules, weak p53 staining correlated with regions of intense STAT5A staining. Interestingly, in a cohort of triple negative breast tumor tissues there was little correlation between regions of p53 and STAT5A staining, likely reflecting a high frequency of p53 mutations that stabilize the protein in these tumors. We thus reveal an unexpected connection between cytokine signaling and p53.